Voicing the strengths of parent caregivers of medically fragile children from the Pacific Islands and the Philippines - Haley, Janice M. (ProQuest Information and Learning Company, 2003)
The growing number of medically fragile children being discharged home to the care of the parent/s and the impact this has on them, demands that health care providers responsibly address the well-being of this population of parent caregivers. Although studies have revealed that this shift to home care greatly impacts the caregiver's quality of life, research is deficient regarding assessment of the strengths of these parents in providing long-term care for their child, and is deplete of parents from Pacific Island and Filipino populations. The literature reveals that parent caregivers have voiced concern about their own future health. The fundamental purpose of this study was to explore the "strengths", both internal and external, that are utilized by parents of children who are medically fragile from the Pacific Island and Filipino cultures in caring for their child. The sample consisted of 6 parents who are the primary care providers for their child. Data generation methods included audio-taped interviews and participant observation. Transcripts and field notes were analyzed qualitatively to yield domains, themes and theme clusters. The domains were beliefs, values and attitudes. Twelve themes emerged: (1) handling emotional feelings, (2) problem solving skills, (3) spirituality, (4) taking care of self, (5) family support, (6) finding meaning to the child's condition, (7) social/community support, (8) positive attitude, (9) resourcefulness, (10) sense of hardiness, (11) focusing on the present, and (12) spending time in nature. The themes were categorized into four theme clusters: positive energy, connectedness, openness to what is and meeting a challenge. The goal of this study was to increase the understanding of parent caregivers of children who are medically fragile, to identify and build on their "strengths" and to empower these parents to utilize their strengths to better take care of themselves and maintain their well-being.--Abstract.